Tasting paradise on earth : Jiangnan foodways - Feng, Jin, 1971- (University of Washington Press, 2019)
"Tasting Paradise on Earth examines the tension between China's fast-forward modernization and its prevalent cultural nostalgia through an interdisciplinary exploration of how key cities in Jiangsu and Zhejiang Provinces in the Lower Yangzi Delta region, or 'Jiangnan, ' preserve culinary inheritance while also revamping it for the new millennium. Throughout Chinese history, food nostalgia has generated cultural currency for individuals. Tasting Paradise on Earth examines literary treatments of Jiangnan foodways from late imperial and twentieth-century China, and demonstrates the metamorphosis of this cultural landscape in contemporary China, with its new platforms for food nostalgia, such as broadcast media and the Internet. It also highlights the role that gender plays in the expression of food nostalgia and the construction of personal and cultural identities. This analysis both sheds light on Chinese modernization and has broader comparative relevance for the study of global food cultures and modernization. It demonstrates that the (re)formation and management of individual and collective identities in a society undergoing massive transformations can be achieved by homely arts such as cooking, in addition to--and perhaps more effectively than--'high' art forms such as literature and music"--